Evolution of fisheries, aquaculture, and crocodile farming governance in Zimbabwe within the Southern African policy context - Utete, Beaven; Mabika, Nyasha (Frontiers in Conservation Science, 2025)
Capture fisheries, crocodile ranching, and aquaculture provide vital food resources for enhanced food security and nutrition and sustain livelihoods in Southern Africa. Conflicting policies, regulations, and institutional overlaps affect the operation and management of capture fisheries, crocodile ranching, and aquaculture, threatening their sustainability. This scoping review examined the evolution of fisheries, aquaculture, and crocodile farming governance from 1890 to 2021 in Zimbabwe within the Southern African policy context. This aims (i) to identify the legal and policy frameworks for capture fisheries, crocodile farming, and aquaculture firms in Southern Africa and Zimbabwe; (ii) to explore the evolution and gaps in the legislation and policies for capture fisheries, crocodile farming, and aquaculture firms in Southern Africa and Zimbabwe; and (iii) to highlight the strengths and future dimensions for developing prudent management policies for fisheries, crocodile ranching, and aquaculture. Five concatenated evolutionary phases, that is, the soft conservation period (1866–1890), the establishment period (1891–1938), the consolidation of fisheries and crocodile conservation period (1938–1961), the quintessential conservation period (1962–1978), and the conservation progression period (1980–2021)—punctuated by persistent neglect of aquaculture and crocodile ranching, institutional overlaps, and the prominent influence of affluent recreational angling societies on fisheries policy development were identified for Zimbabwe. Within Southern Africa, the evolution of fisheries and aquaculture policies has been more rapid for countries with coastal (marine) and inland freshwater resources such as Namibia, Cape Verde, the Comoros Islands, Seychelles, Madagascar, Mauritius, South Africa, and Tanzania. Armed conflicts slowed (or are slowing) down the evolutionary pace of fisheries and aquaculture policies in Angola, Mozambique, and the Democratic Republic of Congo. Aquaculture is still a fledgling industry; thus, development of the relevant consolidated aquaculture and fisheries governing policies is still in its infancy across Southern Africa. This necessitates standalone, harmonized aquaculture and fisheries policies. Zimbabwe, like all Southern African Development Community (SADC) member states, needs to align its fisheries and aquaculture policies with the SADC Fisheries Sector Policy as guided by the Policy Framework and Reform Strategy for Fisheries and Aquaculture in Africa in order to diversify and enhance sustainable fishing dependent livelihoods.